Some constraints on the severity of landslide penetration in sensitive deposits - Carson, M.; Lajoie, Ginette (Géographie physique et Quaternaire, 1981)
Theoretical considerations and case-studies are presented to show that, in many cases, the severity of retrogression of an unstable valley slope, in areas of sensitive muddy sediment, is controlled by the topography of the valley. A formula is offered to predict the distance of retrogression from topographic attributes of valleys. It is suggested that most retrogressive landslides in sensitive sediments involve only limited liquefaction of the spoil, and it is for this reason that retrogression is controlled by this topographic constraint. Those situations in which retrogression stops before this limit is reached are also discussed: one important factor which can determine whether or not such aborted retrogression will occur appears to be the nature of the first-time slide. Those situations in which retrogression can exceed this topographic limit are briefly examined as well: attention is focussed on the importance of spoil liquefaction as a prerequisite for such excess landslide retrogression. Data are presented which indicate that the initial undrained strength of the sediment exerts a major control on the degree of spoil liquefaction. Finally the possibility is considered that some assumed retrogressive failures were in fact flake slides in which the slide mass disintegrated after failure. Such 'retrogressive facsimiles' are considered to be rare.